Penerapan Teknologi IOT untuk Monitoring Keamanan Kandang Ayam Broiler Berbasis Sensor Magnetik dan Mikrokontroler ESP 32 CAM - Ketria Nursabila; Hafni; Muhammad Zen (CV. Hawari, 2026)
The The increase in theft cases along with technological developments demands a more effective security system. By 2025, the broiler chicken coop partner PT. Ciomas Adisatwa experienced a theft case so that an improvement of the security system was needed. This research aims to apply Internet of Things (IoT) technology to monitor the security of broiler chicken coops using magnetic sensors and ESP32-CAM microcontrollers with telegram notifications. The system design is carried out using the waterfall method which includes the stages of needs analysis, design, testing, and implementation. A magnetic sensor is used to detect the movement of the cage door, and then the ESP32-CAM microcontroller processes the signal to activate the alarm and send notifications in real-time via Telegram. The test results show that the system can function properly and is able to improve the safety of the broiler chicken coop.